1998
DOI: 10.1016/s0006-3495(98)77675-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Ba2+ with the Pores of the Cloned Inward Rectifier K+ Channels Kir2.1 Expressed in Xenopus Oocytes

Abstract: Interactions of Ba2+ with K+ and molecules contributing to inward rectification were studied in the cloned inward rectifier K+ channels, Kir2.1. Extracellular Ba2+ blocked Kir2.1 channels with first-order kinetics in a Vm-dependent manner. At Vm more negative than -120 mV, the Kd-Vm relationship became less steep and the dissociation rate constants were larger, suggesting Ba2+ dissociation into the extracellular space. Both depolarization and increasing [K+]i accelerated the recovery from extracellular Ba2+ bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
47
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 27 publications
10
47
1
1
Order By: Relevance
“…Bupivacaine inhibition of GIRK channels was not therefore caused by interference with G protein signaling. Second, bupivacaine inhibition did not show a time-dependent change in inward current or strong voltage dependence that is typical of cationic channel inhibitors that directly occlude the channel pore (50). Third, bupivacaine had no effect on the biochemical binding of G ␤␥ to a fusion protein containing the N-or C-terminal domain of GIRK1, the two regions implicated in G ␤␥ binding and activation (17)(18)(19)(20).…”
Section: Model For Regulation Of Girk Channels By Local Anesthetics Andmentioning
confidence: 94%
“…Bupivacaine inhibition of GIRK channels was not therefore caused by interference with G protein signaling. Second, bupivacaine inhibition did not show a time-dependent change in inward current or strong voltage dependence that is typical of cationic channel inhibitors that directly occlude the channel pore (50). Third, bupivacaine had no effect on the biochemical binding of G ␤␥ to a fusion protein containing the N-or C-terminal domain of GIRK1, the two regions implicated in G ␤␥ binding and activation (17)(18)(19)(20).…”
Section: Model For Regulation Of Girk Channels By Local Anesthetics Andmentioning
confidence: 94%
“…Pronounced inactivation − K½ • 10 ìÒ at −60 mV High affinity block: maximal block with 50 ìÒ at −60 mV Not done Not done Minimal + Kd(0) = 41·7 ìÒ, ì = 0·51; Kd(0) = 62 ìÒ, ì = 0·54 (Shieh et al 1998) Low affinity block: 0 to < 10 % inhibition by 50 ìÒ at −60 mV; Kd(0) = 50·8 mÒ, ì = 1·95, K½ = 457 ìÒ at −60 mV; Kd(0) = 54 mÒ, ì = 1·57 (Abrams et al 1996), K½ = 300 ìÒ to 1 mÒ (Kubo et al 1993) 42·8% reduction with 10 mÒ Ca¥at −60 mV 58·1% reduction with 10 mÒ Mg¥ at −60 mV Minimal Kir2.4, recently cloned from rat brain were not examined, since it is unlikely this molecular species is responsible for K¤-induced dilatations of arteries due to the low sensitivity of the currents to Ba¥ ([K¤]é = 390 ìÒ) (T opert et al 1998). There was significantly more Kir2.1 transcript expressed in coronary arteries than either basilar or mesenteric arteries.…”
Section: Not Donementioning
confidence: 99%
“…Indeed the interaction of divalent cations with Kir channels has for some time been thought to occur via two distinct binding sites; a shallow site that barely senses the membrane electric field, and a deeper one located approximately half-way within the membrane voltage field. Evidence supporting this suggestion come from the works of many researchers (Standen & Stanfield, 1978;Shioya et al, 1993;Reuveny et al, 1996;Sabirov et al, 1997;Shieh et al, 1998) in which channel block by extracellular Mg 2+ and Ca 2+ was found to occur through the shallow site, whereas blockage by Ba 2+ and Sr 2+ was mediated through the deeper one. Mutants of T141 and S165 affect the deeper binding site, whereas the residues R148 or E125, at the outer mouth of the channel (Navaratnam et al, 1995;Doring et al, 1998;Krapivinsky et al, 1998;Topert et al, 1998), are likely to form the shallow site.…”
mentioning
confidence: 88%
“…This characteristic has resulted in Ba 2+ being used extensively in the separation of Kir currents in native membranes (see Stanfield et al, 2002). Inevitably, more detailed investigations of how Ba 2+ blocks cloned Kir channels, including the rat epithelial channel Kir 1.1 (ROMK2, Zhou et al, 1996) and mouse macrophage channel Kir 2.1 (IRK1, Shieh et al, 1998), have followed.…”
Section: Introductionmentioning
confidence: 99%